A LabVIEW module to promote undergraduate research in control of AC servo motors of robotics manipulator - Yahya, Samer; Moghavvemi, Mahmoud; Almurib, Haider A.F.; Al‐Rizzo, Hussain (John Wiley & Sons, 2020)
This paper presents a project-based learning pedagogy for undergraduate mechanical engineering students which integrates traditional hardware-based laboratory with LabVIEW to control the angular position, velocity, and acceleration of AC servo motors of a six-degree of freedom manipulator. The proposed experimental modules have been proved to be very effective in assisting teams of undergraduate students within the Department of Mechanical, Materials and Manufacturing Engineering at the University of Nottingham, Malaysia Campus, who have used the modules in designing a new mechanical structure of a robot during their capstone design project. The proposed pedagogy inspired undergraduate students to publish their first paper based on the outcomes of their project. The focus on this paper is to present how the students' learning experience has been significantly enforced and their role in developing the modules introduced in this paper. Three modules are presented; the first configures a timer to generate a signal that drives the servo motors. The second drives the servo motor to a specific angular position with a constant angular velocity. Finally, the third is used to control the servo motor to follow any desired angular position, velocity, and acceleration. © 2019 Wiley Periodicals, Inc.